Genesis and Evolution of Educational Culture - Elmuradova Surayyo Abdijalilovna (Peerian Journals Publishing, 2022)
This article discusses the genesis and evolution of educational culture. In order to illuminate the current picture of the modern world, first of all, it is necessary to analyze the interdependence of human diversity - education and social diversity from a socio-philosophical point of view. This analysis reveals the forms of social relations in education as a special system of human existence, the essence of the changing socio-legal relations of society on the basis of its functioning.
Keywords: education; culture; evolution; mythological worldview